Dampak Kompetensi Guru dan Peran Motivasi dalam Menentukan Kinerja Guru di Yayasan Pendidikan GMI Imanuel - Retno Dewanti; Tjia Fiechu; Meriana Meriana (Binus Business Review, 2011)
Educational success is largely determined by the performance of teachers in education. This study aims to examine the contribution of teacher competencies and motivation role in determining the teacher performance. The population in this study were teachers GMI Emmanuel Education Foundation by 74 people. Instruments used in this study was a questionnaire enclosed, was tested with test validity and reliability. The method analysis used discriminant analysis, cluster analysis, Regression, and Path Analysis. The results of cluster analysis showed most teachers who have a positive attitude toward the teacher performance variables. The results of path analysis showed that the research hypothesis accepted in the sense that there are significantly contribution among exogen variables and endogen variable.